Intermediation with Costly Bilateral Exchange - Townsend, R. M. (Review of Economic Studies, 1978)
Journal Article Intermediation with Costly Bilateral Exchange Get access Robert M. Townsend Robert M. Townsend Carnegie-Mellon University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 417–425, https://doi.org/10.2307/2297244 Published: 01 October 1978 Article history Received: 01 February 1976 Accepted: 01 October 1977 Published: 01 October 1978